PEMETAAN SOFT SKILLS GURU TAMAN KANAK-KANAK DI KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Mar’atun Sholeha Sholeha; Zulkifli N '; Devi Risma Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to mapping the soft skills of kindergarten teachers at Payung Sekaki District of Pekanbaru City. The population in this research were 123 teachers. The sample in this study was determined by using the formula of Slovin which totaled 94 teachers. The techniques of data collection used is to using a written test and analysis techniques used is using a percentage formula. The results of this research obtaining of the mapping of kindergarten teacher’s soft skills at Payung Sekaki District for personal competence aspects which is in the category of